Enhancing Entisols Physical Properties and Sweet Corn Agronomic Performances with Liquid Organic Fertilizer and Cow Manure - Dwipa, Eliza Rahma; Widiyono, Heru; Murcitro, Bambang Gonggo; Hasanudin; Masdar (BPFP Universitas Bengkulu, 2023)
Entisols, comprising approximately 10.6% of Indonesia's land area, are youthful soils distinguished by sandy texture, loose structure, ample aeration porosity, rapid permeability, low water retention, and diminished organic matter. This study determines the optimal dosages of liquid organic fertilizer and cow manure capable of enhancing the physical attributes of Entisols and the growth and yield of sweet corn plants. Employing a Randomized Complete Block Design (RCBD) with two factors, the research evaluates three doses of cow manure (0 tons ha-1, 5 tons ha-1, and 10 tons ha-1) and four concentrations of liquid organic fertilizer (0 mL L-1, 100 mL L-1, 200 mL L-1, and 300 mL L-1). The findings reveal that liquid organic fertilizer significantly influenced soil wet weight and pF pressure at 0.1 atm (12.68 g-1). Application of cow manure demonstrates tangible improvements in Entisols properties, with water content at 12.15%, bulk density at 0.73 g m-3, permeability at 90.57 cm hour-1, and soil wet weight and pF pressure at 0.1 atm (15.10 g). Furthermore, liquid organic fertilizer contributes to a plant height of 176.82 cm and husk cob weight of 8,545 kg ha-1, while cow manure results in a plant height of 174.05 cm and husk cob weight of 8.044 kg ha-1. The optimal combination emerged with a 300 mL L-1 concentration of liquid organic fertilizer or a 10 tons ha-1 dose of cow manure, showcasing superior enhancements in Entisols' physical properties, as well as sweet corn plant growth and yield.